Accounting in Turkey, yesterday and today. (14th September 2007) - Tenker, Nejat; Tetik, Nilufer
The modern Income Tax Law was introduced to Turkish society in 1950 and shortly after affected accounting practices in such a way that only the income before the tax figure in the income and loss statement became extremely important for companies. The primary role of accounting - providing a true and fair financial and economic picture of a company to society - was almost ignored. The financial statements were incomparable across the years and among the companies for evaluating the companies. These developments forced the professional accounting organisations, the universities and the government institutions of the country to eliminate this unacceptable situation. The need for financial statements prepared under the generally accepted accounting standards increased. Finally, entering foreign markets and inviting foreign investors to Turkey brought the accounting profession to the place where it is today. In the paper we will explain this development in detail.